Quasi-Frobenius rings - Nicholson, W. Keith (Cambridge tracts in mathematics, 2003)
A ring is called quasi-Frobenius if it is right or left selfinjective, and right or left artinian. While the present extent of the theory of these rings is vast, this book provides a self-contained account at a level allowing researchers and graduate students to gain entry to the field.